Psychological distress and academic success: a two-year study comparing the outcome of two online interventions at a university counseling and consultation service in Italy - Mammarella, Silvia; Giusti, Laura; Del Vecchio, Sasha; Salza, Anna; Casacchia, Massimo; Roncone, Rita (Frontiers in Psychiatry, 2024)
Background: The mental health of college students has been a significant concern in higher education, representing a priority for the institutions. Enhancing effective online interventions could represent excellent support for university counseling services that deal with students' well-being. The present study aimed to evaluate the effectiveness of two online interventions provided by the Counseling and Consultation Service for Students (SACS) of the University of L’Aquila (Italy), namely Videochat with Clinical Mental Health consultation (VCMH) and Therapist-supported Internet Cognitive Behavioral Therapy (Ts-iCBT), a 12-module asynchronous program for anxiety management. The primary outcome was focused on the emotional well-being of students (GHQ-12). The secondary academic outcome was represented by the attainment of their final degree. Methods: Students requesting help from the SACS between March 2020 and March 2022 during different periods of the COVID-19 pandemic restrictions were asked to fill out a brief structured screening tool and access the PSYDIT.COM platform. Based on their personal preferences, students chose to access one of the two different online interventions: VCMH and Ts-iCBT. Results: Over the two-year duration of this study, 379 students (267 women, 70.4%) contacted the service. Out of 334 students, 72.5% asked to be included in the Ts-iCBT group, whereas 27.5% expressed a preference for the VCMH group. A statistically significant decrease in emotional distress was obtained by both forms of online intervention, highlighting a better outcome for VCMH. In addition to clinical variables, 28.8% of students who completed online interventions attained their degree, with a statistically significantly higher percentage of graduated students in the Ts-iCBT compared to VCMH group. A high proportion of students (37.7% of total sample) dropped out (DO) of digital interventions, with a statistically significant lower rate of dropouts in the VCMH group. Conclusions: The effectiveness of online interventions is extremely promising and yields a growing source of suggestions for use in providing more tailored interventions. Videochats and frequent therapist online contacts would be recommended for more severe psychopathological conditions. Students in conditions of moderate and non-severe emotional distress who feel more able to "manage the problem alone” could be addressed to asynchronous online interventions.